2017
DOI: 10.1128/msphere.00238-17
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Resolving Fungal Nomenclature: the Case of Multiple Pathogenic Species in the Cryptococcus Genus

Abstract: Cryptococcosis is a major fungal disease caused by members of the Cryptococcus gattii and Cryptococcus neoformans species complexes. After more than 15 years of molecular genetic and phenotypic studies and much debate, a proposal for a taxonomic revision was made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
90
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(94 citation statements)
references
References 148 publications
0
90
1
3
Order By: Relevance
“…Recently, it was suggested that some of these major molecular types should be raised to species level (Hagen et al, 2015). However, the proposed division of these complexes into seven distinct species is still the subject of debate (Hagen et al, 2017;Kwon-Chung et al, 2017) and a recent publication has shown that this proposal is premature (Cogliati et al, 2019). To maintain taxonomic stability, the use of "species complexes" had been proposed as interim solution (Kwon-Chung et al, 2017) and is used herein.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was suggested that some of these major molecular types should be raised to species level (Hagen et al, 2015). However, the proposed division of these complexes into seven distinct species is still the subject of debate (Hagen et al, 2017;Kwon-Chung et al, 2017) and a recent publication has shown that this proposal is premature (Cogliati et al, 2019). To maintain taxonomic stability, the use of "species complexes" had been proposed as interim solution (Kwon-Chung et al, 2017) and is used herein.…”
Section: Introductionmentioning
confidence: 99%
“…It was proposed that C. neoformans should be divided into two species, and C. gattii be divided into five species according to the phylogenetic analysis of 155 isolates (Hagen et al ., ). However, studies with more isolates or analysing more genomes may reveal different classification, and the consensus about the classification system has not been reached yet (Hagen et al ., ; Kwon‐Chung et al ., ). Some authors proposed to use ‘ Cryptococcus neoformans species complex’ and ‘ Cryptococcus gattii species complex,’ which can recognize diversity without confusion (Kwon‐Chung et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Four of the six gene deletions that impacted 17 murine survival were novel. Such bedside-to-bench translational research provides important 18 candidate genes for future studies on virulence-associated traits in human Cryptococcus 19 infections.Even with the best available care, mortality rates in cryptococcal meningitis range from 23 20-60%. Disease is often due to infection by the fungus Cryptococcus neoformans and involves a 24 complex interaction between the human host and the fungal pathogen.…”
mentioning
confidence: 99%
“…These analyses have led to 70 competing species definition proposals. The first proposes classifying strains into seven species 71(two from C. neoformans following the serotypes and five from C. gattii) [18,19]. However, 72 based on an analysis of 2600 strains, which revealed genetic diversity that is not-wholly captured 73 by the seven species proposal [20] the second wants to maintain two groups, delineated as the 74 "C. neoformans species complex" and the "C. gattii species complex" [21].…”
mentioning
confidence: 99%
See 1 more Smart Citation